NON-MEDICAL PRESCRIPTION DRUG USE IN SERBIA: RESULTS FROM THE NATIONAL SURVEY ON LIFESTYLES – SUBSTANCE ABUSE AND GAMBLING - Terzić Šupić, Zorica; Todorović, Jovana; Kilibarda, Biljana; Mravčik , Viktor (Srpski medicinski časopis Lekarske komore, 2023)
Background: Non-medical prescription drug use (NMPDU) of anti-anxiety medications is a growing public health concern. The aim of this study was to examine the prevalence of the use of anti-anxiety medications, as well as the factors associated with the NMPDU of these medications among adults in Serbia. Materials and methods: The study is a secondary analysis of the data from the National Survey on Lifestyles in Serbia – Substance Abuse and Gambling, conducted in 2014 and 2018, with 7,385 participants. Results: The prevalence of prescription only use of anti-anxiety medications was 13.5% (995/7,385), while the prevalence of the non-medical prescription drug use was 5.04% (372/7,385). Multinomial logistic regression analysis showed an association between non-medical prescription use of anti-anxiety medications and the female sex (OR: 3.23), the age between 35 and 44 years (OR: 1.91), the age between 45 and 54 years (OR: 2.40), or the age between 55 and 64 years (OR: 2.97), reporting a low (OR: 2.40) or average (OR:1.67) satisfaction with health status, being a smoker (OR: 1.62), having moderate (OR: 2.35) or high (OR: 4.56) psychological distress, and having a low/moderate risk for pathological gambling (OR: 1.86). Conclusion: There is a clear need for the inclusion of health care professionals and media in the education of patients on the risks of self-medication, medication exchange, or illegal purchase of these medications.